Functional outcomes of internal hemipelvectomy in paediatric patients with malignant bone tumours: a monocentric case series - Junjua, Fateh Ali; Saeed, Javeria; Ali, Moiz; Umer, Masood (Journal of the Pakistan Medical Association, 2025)
A case series was conducted between January 2010 and January 2018, which included 17 paediatric patients under the age of 18 years (mean age 13.4 ±3.53), who underwent internal hemipelvectomy. Functional outcomes were assessed based on gait and categorised as either normal or abnormal. The most common diagnosis was Ewings Sarcoma in 14 patients (82.3%). With regards to reconstruction, acetabular reconstruction was necessary in 1 patient (5.9%), and soft tissue coverage with flaps was required in 5 cases (29.4%). Nerve injury was the most common complication noted, i.e. in 5 cases (29.4%). The disease-free survival rate was 12 patients (70.6%) at a median time of 72 months, while the overall mortality rate was 5 patients (29.4%) with metastatic disease being the leading cause. Hence, it was concluded that internal hemipelvectomy is a viable surgical option in the paediatric population particularly when negative margins can be achieved without compromising the neurovascular structures. Keywords: Tumour, Paediatric, Internal hemipelvectomy.